Evaluating the diagnostic performance of adult sepsis event criteria in the emergency department: impact of including isolated serum lactate elevations - Hyojun Park; Ryoung-Eun Ko; Hyo-Seok Oh; Jae Young Moon; Youjin Chang; Gee Young Suh (Journal of Intensive Care)
Abstract Background The Adult Sepsis Event (ASE) criteria, developed by the US. Centers for Disease Control and Prevention (CDC), utilize electronic Sequential Organ Failure Assessment (eSOFA) scores derived from structured electronic health records to retrospectively detect organ dysfunction in patients with suspected sepsis. While validated primarily in inpatient cohorts, their applicability in emergency department (ED) populations remains uncertain. Moreover, the impact of including isolated serum lactate elevation as a marker of organ dysfunction in eSOFA has not been systematically evaluated. Methods We retrospectively reviewed data from 698 patients (aged ≥ 19 years) with suspected infections presenting to the EDs of three institutions from September 1 to 30, 2023. Blood cultures were obtained from all patients. Patients were classified according to Sepsis-3 (≥ 2-point SOFA score increase from baseline) and ASE-defined eSOFA (organ dysfunction occurring within ± 2 days of blood culture collection). Extended eSOFA additionally included isolated lactate elevation (≥ 2.0 mmol/L). Diagnostic performance was assessed using sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results Among 698 patients, 456 (65.3%) met Sepsis-3 criteria, 251 (35.9%) met ASE-defined eSOFA, and 340 (48.7%) met extended eSOFA criteria. Mortality was highest (19.8%) among patients classified by both SOFA and eSOFA. ASE-defined eSOFA demonstrated moderate sensitivity (52.0%) and high specificity (94.2%), with a PPV of 94.4%. Extended eSOFA improved sensitivity (64.3%) but lowered specificity (80.6%). Mortality increased with the number of dysfunctional organ categories. Notably, the inclusion of isolated lactate elevations identified additional high-risk patients not captured by eSOFA. Conclusion ASE-defined eSOFA moderately aligns with Sepsis-3 criteria, effectively identifying high-risk ED sepsis cases. Extended eSOFA criteria with lactate enhance sensitivity but reduce specificity, suggesting tailored application based on clinical settings and available resources.